2017
DOI: 10.2147/nss.s103467
|View full text |Cite
|
Sign up to set email alerts
|

New developments in the management of narcolepsy

Abstract: Narcolepsy is a life-long, underrecognized sleep disorder that affects 0.02%–0.18% of the US and Western European populations. Genetic predisposition is suspected because of narcolepsy’s strong association with HLA DQB1*06-02, and genome-wide association studies have identified polymorphisms in T-cell receptor loci. Narcolepsy pathophysiology is linked to loss of signaling by hypocretin-producing neurons; an autoimmune etiology possibly triggered by some environmental agent may precipitate hypocretin neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 77 publications
1
57
0
2
Order By: Relevance
“…For this reason, it is important to follow the weight of the narcoleptic children in the follow-up to evaluate the effectiveness of the treatment, not only during the diagnosis. Hyperactive/aggressive behaviour in children, problems in communication with their peers, and rarely psychotic symptoms can be observed [22]. In our patient, improvement was observed in aggressive and nervous behaviours especially towards the family after treatment.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…For this reason, it is important to follow the weight of the narcoleptic children in the follow-up to evaluate the effectiveness of the treatment, not only during the diagnosis. Hyperactive/aggressive behaviour in children, problems in communication with their peers, and rarely psychotic symptoms can be observed [22]. In our patient, improvement was observed in aggressive and nervous behaviours especially towards the family after treatment.…”
Section: Discussionsupporting
confidence: 53%
“…Surprisingly, with the sleep specialists, primary care physicians, and the general public who participated in the AWAKEN study [23], it was found that knowledge and awareness of narcolepsy was very low. It is important to identify the signs of narcolepsy early, to confirm the diagnosis and to make the treatment effective [22]. It is important to remember the diagnosis of narcolepsy in childhood patients who present with symptoms of daytime sleeping and excessive sleepiness, without forgetting that narcolepsy symptoms begin most often in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of GABA in the CNS suggest that GABA plays a major role in various brain and spinal cord functions, and modulation of GABA transmission can significantly affect CNS function. Drugs that target GABA A receptors have been used to treat anxiety, insomnia, and epilepsy; orthosteric GABA B agonists are used to treat muscle rigidity and narcolepsy . Activation of GABA B receptors by systemic administration of the GABA B agonist baclofen induces analgesia, a mechanism that is primarily mediated by GABA B receptors expressed on afferent terminals in the dorsal horn of the spinal cord and that also involves cholinergic and endocannabinoid mediators .…”
mentioning
confidence: 99%
“…Patients on these medications should be followed closely to ensure that blood pressure, pulse, and weight are not negatively affected. 18,50 Addiction and tolerance can develop with these drugs, and follow-up should include assessment for dependence. Some states may require prescription drug monitoring to ensure the drugs are not being abused or diverted.…”
Section: Golden and Lipfordmentioning
confidence: 99%